Antidiarrhoeal activity of ethanolic stem bark extract of Newbouldia laevis in castor oil-induced diarrhoea in rats - Aderinola AA; Ejiofor A; Oyinloye OE; Fasanya TA; Eremu E (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2019)
Background: Diarrhoeal disease is the second leading cause of morbidity and mortality in developing countries requiring urgent attention. Many of the conventional anti-diarrhoeal drugs cause serious adverse effects, hence the need to screen various plants for their medicinal values becomes imperative. Objective: To investigate the anti-diarrhoeal activity of ethanolic stem bark extract of Newbouldia laevis in castor-oil induced diarrhoea in rats. Methods: The stem bark of Newbouldia laevis collected from Abeokuta, Ogun State, was air-dried, ground, macerated in 90% ethanol and concentrated to dryness in a water bath and then reconstituted using distilled water. Fifty (50) albino rats of both sexes used for the study were divided into two groups: A and B with twenty-five (25) rats per group. Group A was used for the gastro-intestinal motility test using charcoal meal while Group B was used for castor-oil induced diarrhoea test and the number of stool pellets was counted over an hour period. Results: The extract (250-1000mg/kg) showed significant (p= 0.0399) anti-diarrhoeal activity by decreasing the distance of the gastrointestinal movement of charcoal meal in the treated rats and also inhibited the severity of diarrhoea induced by castor-oil in a dose-dependent manner when compared with the control (distilled water). This activity could be attributed to phytochemicals like flavonoids and tannins present in Newbouldia laevis. Conclusion: The results showed that stem bark extract of Newbouldia laevis possesses a significant anti-diarrhoeal property and this supports the traditional use of the plant in the treatment of diarrhoea.